00.02: Developments in research and assessment of steel structures: Highlights from the perspective of an American researcher. (13th September 2017) - Schafer, Benjamin William
ABSTRACT: The objective of this paper is to provide a summary of recent developments in the research and assessment of steel building structures. The task is too broad to accomplish in a general sense, as such the perspective and biases of the author as an American research professor who primarily focuses on thin‐walled steel building applications is explicitly recognized. The discussed research is separated into three areas: cold‐formed steel structures, hot‐rolled steel structures, and earthquake engineering for steel structures. The focus of the presentation is on research conducted within each of these three areas, in the last 5 years, primarily in the United States, with particular emphasis on projects that the author was directly involved in or lead. In addition, each area concludes with a brief discussion of developments in American steel codes and standards that are related to the research. Cold‐formed steel structures have enjoyed a large body of recent research, advancements in: modelling, imperfection measurement, stiffness characterization, coupled instabilities, design under multiple actions, and system reliability are all highlighted. The author has had less direct involvement in much of the recent hot‐rolled steel structural research, but serves on the committees where this research is brought into the American standards. Work that has had a specific impact on the American hot‐rolled steel standards in beams, slender columns, composite columns, bracing, fire, and progressive collapse are all highlighted. In addition, recent research advancing modelling for fracture in steel is summarized due to the authors belief in the large long term impact of those efforts. Earthquake engineering for steel structures spans a broad space, highlighted research includes: benchmark tests and building models for cold‐formed steel framing; new tests, modelling, and design guidance on structural steel seismic force‐resisting systems; and new research in steel diaphragm systems. Taken as a whole, the paper aims to demonstrate the vibrancy in American steel building research, now more than 125 years since the first steel‐framed skyscraper.